ANALISIS PENETAPAN MARGIN PADA PEMBIAYAAN MURABAHAH DI KPPS BMT EL-USWAH DHARMASRAYA - Rahmadani Eka Putri; Sandra Dewi (CV. Adiba Aisha Amira, 2024)
This research was motivated by the lack of role of KSPPS BMT El-Uswah Dharmasraya in explaining to customers about determining margins before entering into a financing agreement, resulting in a lack of customer understanding regarding the determination of margins determined by KSPPS BMT El-Uswah Dharmasraya. This type of research is field (filed research) which is descriptive qualitative in nature which is carried out by describing how margins are determined for murabahah financing at KSPPS BMT El-Uswah Dharmasraya. The data collection technique in this research is through interviews by visiting the KSPPS BMT El-Uswah Dharmasraya office directly as well as documentation to obtain written data related to this thesisi. Based on the results of the research conducted, it can be concluded that the margin determination determined by KSPPS BMT El- Uswah Dharmasraya uses a flat calculation method, where the amount of margin given is fixed and does not change. Factors taken into consideration in determining margins at KSPPS BMT El-Uswah Dharmasraya are business factors, level of competition, financing risk and type of customer. Apart from that, there are also factors that influence margin determination, namely profit targets and overhead costs.